LTE efficiency when used in traffic information systems: A stable interest aware clustering - Ahmad, Iftikhar; Noor, Rafidah Md; Reza Z'aba, Muhammad (Wiley, 2018)
Long-term evolution (LTE) technology is critical for the envisioned usage scenarios in the Internet of Vehicles. An important usage scenario is traffic information systems (TIS) for vehicular ad hoc networks (VANETs) that depend on LTE for the delivery of non-safety information to vehicles. TISs are centralized data warehouses that collect and process traffic information and subsequently allow vehicles to receive such information before and during a road trip. Considering the extensive deployment of VANETs, the LTE demand for TIS is expected to increase. Therefore, we explore and quantify the inefficiency of LTE when used in TIS. By envisioning basic test case scenarios, we establish the trends of data usage while commuting and providing insights into how LTE usage in TIS may lead to the inefficient use of the available wireless spectrum during road trips. To reduce identified inefficiency in LTE usage and cluster instability due to the high speed of the vehicles, we proposed a novel stable interest-aware clustering (SIAC) mechanism. SIAC consider VANETs mobility constraint, LTE link quality, and exploit interest of the vehicles, in cluster formation phase. Resulting in the reduction in the data demand of the vehicles and frequency of link failures among the vehicles and provides transmission path stability. SIAC performs well as compared with the existing approaches shows more cluster stability and reduces the LTE usage for driving assistance and route planning applications.